2021
DOI: 10.1002/cncr.33603
|View full text |Cite
|
Sign up to set email alerts
|

Loneliness and symptom burden in oncology patients during the COVID‐19 pandemic

Abstract: BACKGROUND: Loneliness and social isolation are significant public health problems that are being exacerbated during the coronavirus disease 2019 pandemic. Little is known about the associations between loneliness and symptom burden in oncology patients before and during the pandemic. Study purposes include determining the prevalence of loneliness in a sample of oncology patients; evaluating for differences in demographic, clinical, and symptom characteristics between lonely and nonlonely patients; and determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 48 publications
7
38
0
Order By: Relevance
“…We identified that nearly half of the participants (52.2%) met the criteria for loneliness using the UCLA Loneliness Scale. Although this proportion is comparable to a prior study conducted on older adults with cancer during this pandemic, it is higher than the loneliness prevalence of 21–41% reported by pre-pandemic studies conducted among adults with cancer [ 18 , 19 , 26 , 27 ]. This proportion is also substantially higher than the 29% prevalence of loneliness reported among young adults (18–39 years) during the COVID-19 pandemic by a survey conducted by the Centre for Addiction and Mental Health (CAMH) in November 2020 in Canada [ 28 ].…”
Section: Discussionsupporting
confidence: 51%
See 3 more Smart Citations
“…We identified that nearly half of the participants (52.2%) met the criteria for loneliness using the UCLA Loneliness Scale. Although this proportion is comparable to a prior study conducted on older adults with cancer during this pandemic, it is higher than the loneliness prevalence of 21–41% reported by pre-pandemic studies conducted among adults with cancer [ 18 , 19 , 26 , 27 ]. This proportion is also substantially higher than the 29% prevalence of loneliness reported among young adults (18–39 years) during the COVID-19 pandemic by a survey conducted by the Centre for Addiction and Mental Health (CAMH) in November 2020 in Canada [ 28 ].…”
Section: Discussionsupporting
confidence: 51%
“…The presence of high degrees of loneliness and social isolation has been a longstanding issue in AYAs with cancer, but the rising rates during the pandemic as highlighted by our study demonstrate the particular vulnerability of this population to the situations that limit their ability to maintain social connectivity [ 18 , 19 , 26 , 27 ]. As most AYAs with cancer live 50–60 years past their cancer diagnosis with current treatment regimens, and that self-reported loneliness has been associated with increased morbidity and mortality, it is concerning that so many AYAs with cancer identified as lonely in our study [ 9 , 15 ].…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…30 A 5-point Likert scale is used to rate each item from 0 (no problem) to 4 (very severe problem). The total score ranges from 0 to 28 and is interpreted as follows: absence of insomnia (0-7), subthreshold insomnia (8)(9)(10)(11)(12)(13)(14), moderate insomnia (15)(16)(17)(18)(19)(20)(21), and severe insomnia (22)(23)(24)(25)(26)(27)(28).…”
Section: Insomnia Evaluationmentioning
confidence: 99%